POLITIK BAHASA DALAM IQRA - Indrawati Indrawati (Wardah, 2012)
The decline is a sign of the beginning of the iqra literacy commanded Gabriel to educate people. Iqra (read) is a model of language education given to the Prophet Muhammad to be imitated and used as a reference by the developers of the language policy (policy language) in particular and education in general. Politics of language in iqra assert that language acquisition is the basis of all forms of education and preparation of human resources in a country. Thus, in the context of the Indonesia development of language education needs to be addressed through policy wisely national language.